Fibronectin-1 expression is increased in aggressive thyroid cancer and favors the migration and invasion of cancer cells. (15th August 2016) - Sponziello, Marialuisa; Rosignolo, Francesca; Celano, Marilena; Maggisano, Valentina; Pecce, Valeria; De Rose, Roberta Francesca; Lombardo, Giovanni Enrico; Durante, Cosimo; Filetti, Sebastiano; Damante, Giuseppe; Russo, Diego; Bulotta, Stefania
Abstract: In this study we analyzed the expression levels of markers of epithelial-to-mesenchymal transition (EMT) in several papillary thyroid carcinomas (PTCs) and the relation with tumor genotypes and clinicopathological characteristics. The role of fibronectin-1 (FN1) was investigated by analyzing the effects of FN1 silencing in two human thyroid cancer cell lines. Most of EMT markers were significantly over-expressed in a group of 36 PTCs. In particular, FN1 mRNA levels were higher in tumor vs non-tumor tissue (117.3, p < 0.001) and also in aggressive and BRAF V600E samples. Similar results were observed (and confirmed at the protein level) when FN1 expression was analyzed in a validation group of 50 PTCs and six lymph node (LN) metastases. Silencing of FN1 in TPC-1 and BCPAP thyroid cancer cells significantly reduced proliferation, adhesion, migration, and invasion in both cell lines. Collectively, our data indicate that FN1 overexpression is an important determinant of thyroid cancer aggressiveness. Highlights: EMT markers are overexpressed in papillary thyroid cancers. Fibronectin-1 is the marker most highly overexpressed in aggressive tumors. FN1 silencing impairs thyroid cancer cell growth, migration, and invasion.